The Dendritic Cell Dilemma in the Skin: Between Tolerance and Immunity - Scheib, Nils; Tiemann, Jessica; Becker, Christian; Probst, Hans Christian; Raker, Verena Katharina; Steinbrink, Kerstin (Frontiers in Immunology, 2022)
Dendritic cells (DC) are uniquely capable of initiating and directing immune responses. The range of their activities grounds in the heterogeneity of DC subsets and their functional plasticity. Numerical and functional DC changes influence the development and progression of disease, and correction of such dysregulations has the potential to treat disease causally. In this review, we discuss the major advances in our understanding of the regulation of DC lineage formation, differentiation, and function in the skin. We describe the alteration of DC in disease as well as possibilities for therapeutic reprogramming with a focus on tolerogenic DC. Because regulatory T cells (Treg) are indispensable partners of DC in the induction and control of tolerance, we pay special attention to the interactions with these cells. Above all, we would like to arouse fascination for this cell type and its therapeutic potential in skin diseases.